Pedagogia histórico-crítica na rede municipal de educação de Itaipulândia/Pr (2004-2016) - Viana, Eliane (2017)
The Historical-Critical Pedagogy, since its inception in 1979, represents an instrument of analysis, resistance and struggle within the framework of economic, political, social and educational relations. Because it is a counter-hegemonic pedagogy, it exerts a fundamental role in the current context, because the educational problems in the developing countries intensify the (re) structuring of the productive system, resulting in reforms and changes in the curricular guidelines for the Basic Education In Brazil since the 1990s, based on the pedagogies of the learning to learn, with views for the training of the worker and consumer required for the reproduction of the capital. Thus, there is an intensive cheapening of the school education aimed at the working class and the loss of its specificity, that is, of the centrality in the transmission-assimilation of the objective knowledge converted into scholarly knowledge, because this is fundamental for the means of the explication of the exploration relations and , thus, to the process of social transformation. In the face of the educational problematics, this Marxist pedagogy stands as a theoretical-methodological instrument, and, contradictorily, its foundations are present in official documents of education departments of some municipalities, mainly in Paraná and São Paulo, with the experience of Itaipulândia one of them. Therefore, our research has as general objective to explain the historical process of implantation, implementation and understanding of the Historical-Critical Pedagogy in the municipal education network of Itaipulândia / PR in the temporal cut from 2004 to 2016. It parts of the following problem: What is the specificity of the Historical-Critical Pedagogy in the Itaipulândia municipal teaching network regarding its implementation, implementation and understanding process? We start from the assumption that the curricular pedagogical proposal and the actions of the municipal education network of Itaipulândia / PR are based on the historical-critical perspective, obtaining from the documentary analysis the confirmation of the initial hypothesis. Therefore, in the theoretical aspect they contradict the national curricular guidelines. In the same way, the educational trajectory of this perspective in the municipality reveals that the actions with the finality of to effect its answer to the needs of each historical moment and are realized according to the material conditions they face, as well as, from the experiences in the the state and regional levels. This course in the municipality explains the class struggle and represents a fundamental historical accumulation for the analysis of those who defend the importance of the school education for the huma. development full of meaning, as well as, for the process of social transformation.